Representações de pessoas com HIV/AIDS sobre o corpo: a construção da corporeidade - Ana Monica Serakides Ivo (2012)
The availability of antiretroviral drugs (ARD) has brought positive changes in the framework of the aids epidemic in Brazil in relation to complications with HIV and the consequent decrease in mortality, transforming aids in a chronic disease. However, it has brought, also, challenges for people living with HIV/aids (PLWHA), such as, adherence to treatment, body changes and important changes in social interactions. These challenges are experienced differently by PLWHA and may be presented as difficulties that directly interfere in social interactions. The body expressed in social, understood as corporeality, allows the constitution of identity and identification of the subjects. The corporeality, constituted in the trajectories of life, contains representations on the body at the same time that expresses them. In spite of sociology and epidemiology great advances in the knowledge of social experience of people infected and their contribution to the improvement of health care of PLWHA, the knowledge about the experiences of the body has been little explored. The objective of this study is to understand representations of people with HIV/aids on the body and its interactions, after the diagnosis of infection. The approach was qualitative and based on the theory of social representations. Data collection was performed by in-depth interviews with PLWHA, in a reference service in HIV/aids, in Belo Horizonte, Minas Gerais. The interpretation of data took place by means of structural analysis of narration, which allowed the construction of three categories: a) Representations on aids and medication use; (b) Representations on infected and sick body; c) Representations on corporeality: social interactions and body; grouped into a theoretical category, that was entitled Visibility and Secret. The interpretation of the data showed the permanence of the representation of aids as a deadly and transmissible disease, on which there is guilt and fear to infect other people. The fear of body changes is associated with both the infection and the use of antiretroviral drugs, because they can give visibility to the disease. The secret about the disease appears as the keeper of family, professional, sexual and affective relations. The representations of the infected or sick body break, therefore, with those that make the person feel reliable, beautiful and desirable, and, even if there are no apparent changes, corporeality is modified along the experience of disease.